Pengaruh Kepemimpinan dan Komunikasi terhadap Kinerja Pegawai melalui Motivasi Kerja sebagai Variabel Intervening pada UPTD Puskesmas Kuta Tinggi Kecamatan Simpang Kanan Kabupaten Aceh Singkil - Manik, Eka Kristina; Bangun, Nirwana Br; Hiya, Nirmadarningsih (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to determine the effect of leadership and communication on employee performance through work motivation as an intervening variable at UPTD Puskesmas Kuta Tinggi, Simpang Kanan District, Aceh Singkil Regency. The research method used is a quantitative method with data collection techniques through distributing questionnaires to employees. The population in this study consisted of all employees of UPTD Puskesmas Kuta Tinggi totaling 85 people, and the entire population was used as the research sample using a saturated sampling technique. Data analysis was carried out using the SPSS version 30 program through validity tests, reliability tests, classical assumption tests, t-tests (partial), coefficient of determination tests (R²), and path analysis. The results of the study indicate that leadership has a significant effect on employee performance, communication has a significant effect on employee performance, and work motivation has a significant effect on employee performance. In addition, leadership and communication also have a significant effect on work motivation. The results of the path analysis show that work motivation is able to mediate the effect of leadership and communication on employee performance. Thus, it can be concluded that good leadership and communication can increase employee work motivation, which in turn has an impact on improving employee performance at UPTD Puskesmas Kuta Tinggi, Simpang Kanan District, Aceh Singkil Regency.